How did XF-ACTORS contribute to the work of NPPOs - Petter, Françoise; Giovani, Baldissera; Picard, Camille; Tanner, Rob; Vicent, Antonio (2022)
The European and Mediterranean Plant Protection Organization (EPPO) is a regional standard-setting organization in plant health. One of EPPO’s main priorities is to prevent the introduction of dangerous pests from other parts of the world, and to limit their spread within the region should they be introduced. After the introduction of Xylella fastidiosa in the region, the first priority for the organization has been the revision of the Diagnostic protocol (first adopted in 2004). Standards on inspection of consignments and place of production have also been prepared.